Acute ingestion of rosemary water: Evidence of cognitive and cerebrovascular effects in healthy adults. (December 2018) - Moss, Mark; Smith, Ellen; Milner, Matthew; McCready, Jemma
Background: The use of herbal extracts and supplements to enhance health and wellbeing is increasing in western society. Aims: This study investigated the impact of the acute ingestion of a commercially available water containing an extract and hydrolat of rosemary ( Rosmarinus officinalis L. syn. Salvia rosmarinus Schleid.). Aspects of cognitive functioning, mood and cerebrovascular response measured by near-infrared spectroscopy provided the dependent variables. Methods: Eighty healthy adults were randomly allocated to consume either 250 mL of rosemary water or plain mineral water. They then completed a series of computerised cognitive tasks, followed by subjective measures of alertness and fatigue. Near-infrared spectroscopy monitored levels of total, oxygenated and deoxygenated haemoglobin at baseline and throughout the cognitive testing procedure. Results: Analysis of the data revealed a number of statistically significant, small, beneficial effects of rosemary water on cognition, consistent with those found previously for the inhalation of the aroma of rosemary essential oil. Of particular interest here are the cerebrovascular effects noted for deoxygenated haemoglobin levels during cognitive task performance that were significantly higher in the rosemary water condition. This represents a novel finding in this area, and may indicate a facilitation of oxygen extraction at times of cognitive demand. Conclusion: Taken together the data suggest potential beneficial properties of acute consumption of rosemary water. The findings are discussed in terms of putative metabolic and cholinergic mechanisms.